The synthesis of silica nanoparticles via sol-gel process, characterization and cytotoxicity study on the peripheral blood mononuclear cells (PBMC), osteoblast (hFOB) and its cancerous counterpart osteosarcoma (U2OS) - Antonins, Samson (Universiti Sains Malaysia, 2015)
Sol-gel process is one of the most developed common way of synthesizing silica nanoparticles. However the information of its toxicity impact on human cell lines was still very much limited especially towards peripheral blood mononuclear cells (PBMC), osteoblast (hFOB) and its cancerous counterpart osteosarcoma (U2OS). Therefore, this study was conducted to synthesize silica nanoparticles via modified sol-gel processing followed by particle characterization and lastly testing its biocompatibility towards the previously mentioned cell lines. Silica nanoparticles synthesized via sol-gel process consist of 6 different sets, the first set was set up as a standard, followed by the remaining five which vary in terms of concentration of the precursor tetraethylorthosilicate (TEOS), ratio of distilled water to precursor (TEOS), feed rate of pure ammonia and multiple modifications of parameters at once respectively. Characterization were done using Fourier Transform Infrared Spectroscopy and Scanning Electron Microscope. In vitro cytotoxicity testing which assess the cell viability of PBMC, hFOB and U2OS was done in a dose-dependent manner. Cytotoxicity is measured in terms of IC50. The toxicity of the smaller-sized nanoparticles (32.95nm-45.45nm) were higher towards osteosarcoma however lower value towards PBMC cell lines. Bigger-sized nanoparticles (65.05nm- 83.44nm) on the contrary have lower toxicity levels towards osteosarcoma and higher towards PBMC. On osteoblast, most of the IC50 value could not be determined. These results shows that the cytotoxicity of nanoparticles does not relate to its size in a straightforward manner. In fact, size-dependent cytotoxicity in various study have shown a contradictory results. Plausible explanation, is that cytotoxicity of silica nanoparticles also dependent on the metabolic activity of the cells as different cell lines have different physiological function and their interaction with nanoparticle can be considerably different